Expressed Emotion in the Family: A Meta-Analytic Review of Expressed Emotion as a Mechanism of the Transgenerational Transmission of Mental Disorders - Fahrer, Julia; Brill, Nathalie; Dobener, Lisa Marie; Asbrand, Julia; Christiansen, Hanna (Frontiers in Psychiatry, 2022)
Background: High Expressed Emotion (HEE) has been identified as a risk factor for the exacerbation and course of mental illness. EE has been investigated as a caregiver’s response to an offspring’s problem behavior and pathology. The present meta-analysis regards EE from a transgenerational perspective and as one mechanism that might explain the transgenerational transmission of mental disorders. Method: We identified a total of 13 studies relying on 16 independent samples of parent-child dyads of parents with a mental illness and healthy controls; these were included in our analysis. Results are synthesized into one effect sizes per sample, and meta-regression on additional effects of parental diagnostic category; child mental illness and child age were also applied. Results: Parents with a mental illness are classified as HEE significantly more often. Effects were established for high criticism, albeit of small size (OR = 1.45), though they become stronger whenever offspring exhibit mental illness themselves (OR = 2.82). Conclusion: The current study highlights the dearth of studies on EE in families in which a parent has a mental illness and its effects on their children. Our findings highlight EE as a potential mechanism for attributing the transgenerational transmission of mental disorders, especially for the EE-variable criticism indicating dysfunctional parent-child interactions.